Vascular Diseases for the Non-Specialist : An Evidence-Based Guide - Navarro, Tulio Pinho; Dardik, Alan; Junqueira, Daniela; Cisneros, Ligia (Springer International Publishing : Imprint: Springer, 2017)
This book aims to provide non-specialist healthcare practitioners with current, focused and objective information on the most common vascular diseases encountered in daily clinical practice. In day-to-day clinical practice many healthcare practitioners do not have a working knowledge of the most common vascular diseases that frequently arise in patient care. Some of these topics include: aneurysms, peripheral arterial disease, diabetic foot, venous thromboembolism, cerebrovascular disease, aortic dissection, and acute limb ischemia. These commonly encountered vascular diseases are becoming public health issues due to their high morbidity and mortality as well as increasing healthcare costs. Since patients with vascular diseases are often referred to non-specialists, the general practitioner must know how to proper handle the most common vascular diseases encountered in daily clinical practice. For each disease the concept, epidemiology, natural history, diagnosis and treatment are described, followed by essential advice on what the non-specialist can do for the patient and when to refer the patient to a specialist.
Keywords: Medicine.; Vascular surgery.; elektronické knihy; electronic books